Application Of Audio Visual Media In Indonesian Language Subjects To Improve Learning Outcomes Of Class V Students Of SD Negeri 74 Bengkulu City - Hidayani, Resma Nur; Putri , Faizah Nabilah; Indriani , Ikka Aprilia; Irnanda , Annisha Shabrina; Futri , Rahmatika; Agusdianita , Neza (Utami Publisher, 2025)
The research aims to determine the improvement in students' Indonesian language learning outcomes in procedural text material through the use of learning video media. The low value of student learning outcomes compared to the Learning Goal Achievement Criteria (KKTP) was the reason for conducting this research. This research uses a Classroom Action Research (PTK) approach with the Kemmis MC Taggart model which consists of planning, implementation, observation and reflection. Data is taken through observation, tests, interviews and documentation. The research was conducted on class VD students at SD Negeri 74 Bengkulu City with a total of 31 students as respondents. The indicator of success in this research is that 70% of students can achieve a KKTP of 60. The pre-cycle results show that only 3 (9.7%) students achieved a KKM of 60 out of 31 students. Through the use of learning video media, in cycle I the results were obtained as many as 15 (48.8%) students achieved the KKTP, while in cycle II the data obtained as many as 29 (93.5%) students achieved the KKTP. Thus, there was a significant increase in the results from pre-cycle I, and from cycle I to cycle II. Based on research results which show an increase in classical learning completeness, which was originally 9.7% in the pre-cycle, then increased to 48.8% in cycle I, and increased to 93.5% in cycle II. Therefore, this research concludes that the use of audiovisual media in the form of learning videos can improve Indonesian language learning outcomes in procedure text material for the class V.